Jacalin Attenuates Colitis-Associated Colorectal Carcinogenesis by Inhibiting Tumor Cell Proliferation and Intestinal Inflammation - Veronez, Luciana Chain; da Silveira, Denise Sayuri Calheiros; Lopes-Júnior, Luis Carlos; dos Santos, Jéssica Cristina; Barbisan, Luis Fernando [UNESP]; Pereira-da-Silva, Gabriela (Oxford University Press (OUP), 2025)
BACKGROUND: Colorectal cancer (CRC) remains a significant cause of morbidity and mortality worldwide. In patients with inflammatory bowel disease, who have twice the risk of developing CRC, chronic inflammation has been recognized to contribute to colitis-associated cancer (CAC) development. Jacalin, a lectin extracted from jackfruit seeds, has been shown to recognize altered glycosylation and to exert antiproliferative and cytotoxic effects in CRC. However, its activity in CAC remains unknown. Herein, we sought to investigate the effects of jacalin in CAC progression using the dextran sulfate sodium (DSS) and azoxymethane (AOM) mouse model. METHODS: Colitis-associated cancer induction was performed in male C57BL/6 mice by an intraperitoneal injection of AOM, followed by 3 cycles of 2.5% DSS diluted in drinking water for 7 days, intercalated by 2 weeks of normal drinking water. After 1 week of daily pretreatment, mice were orally treated with phosphate-buffered saline (control group), 100 or 500 µg of jacalin three times a week for an additional 11 weeks. RESULTS: We showed that jacalin-treated mice presented tumors with reduced volumes and mean size compared to the control group. In addition, both doses of jacalin reduced the number of proliferating cells (Ki-67 positive cells) in tumor tissues, while the higher dose (500 µg) showed also a similar effect in "normal-appearing" colonic crypts. Jacalin treatment attenuated the clinical scores of inflammations, which was accompanied by a reduction of intestinal and/or tumoral production of IL-1β, IL-23, and IL-17. CONCLUSIONS: Collectively, our findings demonstrated that jacalin suppresses CAC development, highlighting its anti-inflammatory and antitumoral role in the AOM/DSS-induced model.